An Application of Reverse Transcriptase Polymerase Chain Reaction in A Relative Quantification of Gene Expression - Santoso, Adi (Annales Bogorienses, 2025)
The ability to quantify steady state levels of individual messenger-RNA (mRNA) transcripts has been the key issue for study on the control of gene expression. Although two available techniques, Northern blot and nuclease protection assays (NPA) have been widely used tor detecting mRNA, these techniques have critical limitations. The most obvious limitation of these two techniques is the required number of target mRNAs to be detected. Reverse transcription-polymerase chain reaction (RT-PCR), which has been accepted as a highly sensitive and specific method, provides a means for detecting and quantifying gene expression using, theoretically only a single molecule of mRNA. The sensitivity and reliability of RT-PCR is dependent upon both the RT and PCR steps. The PCR step has been problematic because of the exponential nature of this reaction where small variation can lead to dramatic changes in final result. Therefore, the use of RT-PCR for quantification of gene expression requires pre-experimental planning and design. In this experiment, the procedure for pre-experimental planning, linear range determination and subsequent relative quantification of gene expression are described in detail. A study of ornithine decarboxyJase gene, a gene involved in the polyamine biosynthesis and temporally expressed, during embryogenesis of Musca domestica (housefly) was used as the model. The results show that during early embryogenesis (t-1 to t-4) the expression level was very low. The increase in expression profile was observed started at t-5, peaked at t-9, and followed by substantial decrease from t-10 to t-12.